Mechanical Properties and Thermal Neutron Absorption of Heavyweight Hematite Aggregate Concrete for Radiation Shielding - Ekhwan Razali, Mohd; Hamid, Roszilah; Abdullah, Yusof (International Journal of Engineering and Technology, 2019)
Heavyweight aggregate concrete (HWAC) is the most widely used material as radiation shielding for nuclear reactors. The density of HWAC is increased through the use of heavy natural aggregates such as barites, hematite and magnetite. This study determines the density of HWAC with hematite aggregate replacing granite at 0%, 10%, 20%, 30%, 40% and 50%, its compressive strength and thermal neutron absorption of 1 MeV fast neutrons. The physical properties of hematite which include gradation, specific gravity, water absorption and loose unit weight are determined. The chemical composition of hematite is also determined using X-ray fluorescent (XRF) analysis. The slump, density, compressive strength and thermal neutron absorption of the heavyweight concrete containing different proportion of hematite as aggregate are also determined. Results show that the slumps of HWAC are between 77 mm â€“ 84 mm, the density of HWAC increases between 0.3% - 1.18% by increasing the hematite content. HWAC with 10% hematite exhibits highest strength at 52.5 MPa and the highest thermal neutron absorption at 2085 count per second. The optimum amount of hematite to replace granite for best strength and neutron absorption is 10%.Â